Bacteroides acidifaciens and its derived extracellular vesicles improve DSS-induced colitis - Zheng, Cihua; Zhong, Yuchun; Xie, Jian; Wang, Zhuoya; Zhang, Wenming; Pi, Yiming; Zhang, Wenjun; Liu, Li; Luo, Jun; Xu, Wei (Frontiers in Microbiology, 2023)
Introduction “Probiotic therapy” to regulate gut microbiota and intervene in intestinal diseases such as inflammatory bowel disease (IBD) has become a research hotspot. Bacteroides acidifaciens, as a new generation of probiotics, has shown beneficial effects on various diseases. Methods In this study, we utilized a mouse colitis model induced by dextran sodium sulfate (DSS) to investigate how B. acidifaciens positively affects IBD. We evaluated the effects ofB. acidifaciens, fecal microbiota transplantation, and bacterial extracellular vesicles (EVs) on DSS-induced colitis in mice. We monitored the phenotype of mouse colitis, detected serum inflammatory factors using ELISA, evaluated intestinal mucosal barrier function using Western blotting and tissue staining, evaluated gut microbiota using 16S rRNA sequencing, and analyzed differences in EVs protein composition derived from B. acidifaciens using proteomics to explore how B. acidifaciens has a positive impact on mouse colitis. Results We confirmed that B. acidifaciens has a protective effect on colitis, including alleviating the colitis phenotype, reducing inflammatory response, and improving intestinal barrier function, accompanied by an increase in the relative abundance of B. acidifaciens and Ruminococcus callidus but a decrease in the relative abundance of B. fragilis. Further fecal bacterial transplantation or fecal filtrate transplantation confirmed the protective effect of eosinophil-regulated gut microbiota and metabolites on DSS-induced colitis. Finally, we validated that EVs derived from B. acidifaciens contain rich functional proteins that can contribute to the relief of colitis. Conclusion Therefore, B. acidifaciens and its derived EVs can alleviate DSS-induced colitis by reducing mucosal damage to colon tissue, reducing inflammatory response, promoting mucosal barrier repair, restoring gut microbiota diversity, and restoring gut microbiota balance in mice. The results of this study provide a theoretical basis for the preclinical application of the new generation of probiotics.